Synthesis of a branched star copolymer by aqueous SET-LRP and its thermo-stimuli response. Issue 4 (2nd April 2020) - Wang, Ling; Ding, Wei; Song, Kaoping; Dong, Chi; Chen, Meixin; Zhou, Huajian
Abstract: Thermally responsive star-shaped polyacrylamides have been efficiently synthesized by copolymerization of acrylamide (AM) with AM-based macromonomer (MPAD) by single-electron-transfer living radical polymerization. Copolymerizations using Gly-Br3 as an initiator were catalyzed by full in situ disproportionation of CuBr/Me6 TREN to Cu(0) powder and CuBr2 and were performed in H2 O at 25 °C. The polymerization proceeded smoothly, and the time dependence of ln([ M ]0 /[ M ]) was linear, implying that the copolymerization was a living polymerization. The polymer products were characterized by FTIR spectroscopy, 1 H NMR spectrometry, and atomic force microscopy. The responsiveness of the water-soluble star-shaped copolymers were studied by turbidity measurements, dynamic light scattering, and transmission electron microscopy. The lower critical solution temperature of a random copolymer can be tuned by changing the feed ratio of MPAD in its synthesis. The phase transition temperature of the copolymer decreased with increasing MPAD content. At a feed ratio of MPAD of 10%, the copolymer obtained exhibited a strong thermal response and could form vesicles. Graphical Abstract: